(untitled) (Canadian Dermatology Today, 2024)
The global response to the COVID-19 pandemic involved rapidly developing and distributing various vaccines to curb the spread of the SARS-CoV-2 virus. While these vaccines are effective in preventing severe illness and hospitalization due to COVID-19, they have also prompted rigorous monitoring for potential side effects and adverse events. Among the vast array of reported post-vaccination side effects, the emergence or worsening of dermatological conditions has attracted significant attention from both clinicians and researchers.